Indicators for assessing Indonesia’s Javan rhino National Park vulnerability to climate change - Purnomo, H.; Herawati, H.; Santoso, H. (2011)
Climate change is already affecting ecosystems in protected forest areas. The Intergovernmental Panel on Climate Change (IPCC) has predicted its impacts will accelerate rapidly over the coming decades. The components of vulnerability have been defined as exposure, sensitivity and the capacity to adapt to climate change. Vulnerability, however, is not an easy concept for policy makers, local communities and other affected stakeholders to understand. This paper illustrates the use of participatory processes in understanding climate change adaptation and defines indicators for assessing the vulnerability of the Javan rhino's national park habitat in Indonesia. The processes generated local vulnerability indicators, organised hierarchically as principles, criteria and indicators (PCIs). While vulnerability principles and criteria were pre-determined and globally defined, the indicators were designed to address the local context. We found the PCIs to be practical tools for communicating vulnerability and for multi-stakeholder dialogues on vulnerability to climate change.